Analisis Efektivitas Pembelajaran Sejarah Kebudayaan Islam terhadap Belajar Siswa di Madrasah Tsanawiyah Negeri 6 Sragen - Sri Isniyati Rahayu; Ngatmin Abbas (CV. Creative Tugu Pena, 2024)
The Islamic Cultural History (SKI) education at MTsN 6 Sragen plays a crucial role in shaping students' understanding of Islamic history and cultural values. This study aims to analyze the effectiveness of SKI learning implementation and identify the supporting and inhibiting factors in the learning process. A qualitative research method with a descriptive approach was employed. Data were collected through observations, interviews with the head of the madrasa, teachers, and students, as well as documentation studies. The findings reveal that SKI learning still faces significant obstacles, such as limited facilities, inadequate teacher training, and low student engagement. However, there are supporting factors that can be optimized, such as the teachers' commitment, school management support, and active participation of parents. The implications of these findings highlight the need for developing more interactive and integrative teaching strategies, enhancing teacher competencies through relevant training, and providing adequate learning facilities. With these efforts, the implementation of SKI learning at MTsN 6 Sragen is expected to be more effective in achieving its educational goals, namely enhancing students' understanding and internalization of Islamic cultural history values.